Conceptual approaches to the classification of budget expenditures for the implementation of public-private partnership projects - Irina B. MAKEEVA (Finance and Credit, 2026)
Subject. Methodological aspects of classifying budget expenditures in the sphere of public-private interaction (PPI). Objectives. Based on the classification of budget expenditures in the sphere of PPI, to identify budget constraints and to formulate proposals for improving the practice. Methods. The following general scientific methods were used: analysis, synthesis, deduction, comparison, and generalization. Results. It is proposed to amend the current regulatory legal acts, which will make it possible to eliminate the additional financial burden on local budgets in the sphere of PPI. Conclusions. Equating concession with subsidy distorts the fundamental principles of PPI and reduces the effectiveness of interaction between the state and business.